Glycosaminoglycans from Litopenaeus vannamei Inhibit the Alzheimer’s Disease β Secretase, BACE1 - Mycroft-West, Courtney J.; Devlin, Anthony J.; Cooper, Lynsay C.; Guimond, Scott E.; Procter, Patricia; Guerrini, Marco; Miller, Gavin J.; Fernig, David G.; Yates, Edwin A.; Lima, Marcelo A.; Skidmore, Mark A. (Marine drugs, 2021)
Only palliative therapeutic options exist for the treatment of Alzheimer’s Disease; no new successful drug candidates have been developed in over 15 years. The widely used clinical anticoagulant heparin has been reported to exert beneficial effects through multiple pathophysiological pathways involved in the aetiology of Alzheimer’s Disease, for example, amyloid peptide production and clearance, tau phosphorylation, inflammation and oxidative stress. Despite the therapeutic potential of heparin as a multi-target drug for Alzheimer’s disease, the repurposing of pharmaceutical heparin is proscribed owing to the potent anticoagulant activity of this drug. Here, a heterogenous non-anticoagulant glycosaminoglycan extract, obtained from the shrimp Litopenaeus vannamei, was found to inhibit the key neuronal β-secretase, BACE1, displaying a more favorable therapeutic ratio compared to pharmaceutical heparin when anticoagulant activity is considered.